Analysis of Dipylidium caninum tapeworms from dogs and cats, or their respective fleas: Part 2. Distinct canine and feline host association with two different Dipylidium caninum genotypes - Beugnet, Frédéric; Labuschagne, Michel; Vos, Christa de; Crafford, Dionne; Fourie, Josephus (Parasite (Paris), 2018)
Initial investigations suggested the existence of two distinct genotypes of Dipylidium caninum from infected cat fleas ( Ctenocephalides felis ). One genotype was found almost always (> 95%) in fleas collected from, and proglottids shed by, domestic dogs. The other was found almost always (> 95%) in fleas collected from, and proglottids shed by, domestic cats. Molecular investigations (Part 1, in this journal) confirmed the presence of two distinct genotypes. Due to the apparent host association observed, these were referred to as the “ D. caninum canine genotype” and the “ D. caninum feline genotype”. The current article reports on an in vivo experimental infection study assessing the host-parasite interaction for each genotype. Mixed infections with the two genotypes in both dogs and cats were conducted. The specific genotyping of proglottids allowed us to assess the specific prepatent periods, prolificity, and longevity of each genotype in dogs versus cats. The possible hybridisation was also studied through molecular evaluation of the proglottids expelled by infected dogs and cats. Results demonstrate a clear distinct host interaction. The canine D. caninum genotype occurred at a higher frequency in dogs, with a shorter prepatent period and a longer lifespan; and the feline genotype occurred at a higher frequency in cats, with a shorter prepatent period and a longer lifespan. The absence of any hybrids in the mixed infections of both dogs and cats confirm the hypothesis of two distinct genotypes, suggesting the possibility of two distinct species within Dipylidium caninum . Des investigations initiales ont suggéré l’existence de deux génotypes distincts au sein de Dipylidium caninum issus de puces infectées ( Ctenocephalides felis ). Un génotype est trouvé dans plus de 95 % des cas chez des puces ou des proglottis collectés sur des chiens. L’autre est trouvé dans plus de 95 % des cas sur des puces collectées sur des chats ou des proglottis éliminés par les chats. Les investigations moléculaires publiées (Partie 1, dans ce journal) ont confirmé l’existence de ces deux génotypes. Du fait de l’apparent tropisme d’hôte, ces deux génotypes sont désignés comme génotype canin et génotype félin. Le présent article présente les résultats d’infestations expérimentales ayant pour objectif d’étudier l’interaction hôte-parasite pour chaque génotype. Des infestations mixtes ont été réalisées avec les deux génotypes chez des chiens et des chats. Le génotypage spécifique a permis d’étudier les périodes prépatentes, la prolificité et la longévité de chaque génotype chez chaque hôte. La possible hybridation a aussi été étudiée par évaluation moléculaire des proglottis éliminés par les chiens et les chats infestés. Les résultats ont démontré une interaction hôte-parasite bien distincte. Le génotype canin de D. caninum a une fréquence plus élevée chez les chiens, avec une période de prépatence plus courte et une durée de vie plus longue, et le génotype félin a une fréquence plus élevée chez les chats, avec une période prépatente plus courte et une durée de vie plus longue. L’absence de tout hybride dans les infections mixtes des chiens et des chats confirme l’hypothèse de deux génotypes distincts, suggérant la possibilité de deux espèces distinctes au sein de Dipylidium caninum .